The long-run relationship between exchange rate and economic growth: the case of sri lanka - Tharsika, K. (Jaffna Science Association, 2024)
The Sri Lankan government is currently contending with a severe economic crisis stemming from inadequate government policies and the aftermath of the COVID-19 pandemic, resulting in a notable deceleration in Sri Lanka's GDP growth. It is imperative for the Sri Lankan government to develop a comprehensive plan aimed at rejuvenating GDP growth. There exists a notable research gap regarding the relationship between exchange rates and economic growth in emerging countries, specifically within the Sri Lankan context. This study seeks to address this gap by investigating the long-run relationship between exchange rate volatility and economic growth in Sri Lanka. The dependent variable, economic growth, is measured through the quarterly percentage change in GDP. The independent variable, the exchange rate, is denoted in US dollars (USD) per Sri Lankan rupee. Data for the study were sourced from the World Bank, Sri Lankan economic and social statistics, and the Central Bank's monthly bulletin. The research methodology involves employing unit root tests and autoregressive distributive lag analysis to fulfill the research objectives. The results note that exchange rate fluctuations have a negative impact on Sri Lanka's economic growth in the long run. This highlights the critical need for the Sri Lankan government and policymakers to formulate and implement effective exchange rate policies aimed at fostering sustained economic growth.
Keywords: Autoregressive Distributive Lag; Economic Growth; Exchange Rate; Sri Lanka